Ice Cream Characteristic with Cured Egg Yolk Powder As Whipping Cream Replacer (Faculty of Animal Science Universitas Brawijaya, 2021)
Ice cream is a dairy product with high calorie because of fat and sugar content. Common sources of ice cream fat include butter, cream, and whipping cream. Cured egg yolk can be used as an alternative to salting eggs in a shorter time to extend the shelf life of eggs. Yolk has a high enough fat content, so it can be used to substitute fat sources in ice cream making.The purpose of this study was to determine the characteristics of ice cream with cured egg yolk powder as a substitute for whipping cream. This study used cured egg powder as a substitute for whipping cream in ice cream. This research consisted of 2 types of cured egg yolk powder (chicken and duck) and 3 levels of cured egg yolk powder substitution (0%, 2%, and 4%) in whipping cream. The analysis of this research was to physical, chemical, and sensory analysis of ice cream. The results showed that the substitution of whipping cream with cured egg yolk powder had a significantly different effect (P <0.05) on fat content and melting point, but not significantly different on moisture, ash, protein, overrun, and sensory ice cream content. The mean moisture, ash, protein content, and ice cream overrun percentage were 58.64%; 1.07%; 5.30%; 39.41%. The average fat content and the melting rate of ice cream with 0 substitutions; 2; 4% cured egg yolk powder successively 9, 29% fat content; 10.39%; 11.13%, while the melting point is 12.43% successively; 21.81%; 30.43%. Based on the research results, it can be concluded that the substitution of 2% - 4% with cured egg yolk powder can increase fat content and melting point without affecting the sensory properties of ice cream, and same with ice cream’s quality standard according to SNI. Duck egg of cured egg yolk powder as whipping cream replacer showed highly overrun content than chicken egg of cured egg yolk powder.